2014
DOI: 10.1095/biolreprod.114.120659
|View full text |Cite
|
Sign up to set email alerts
|

Altered Protein Expression Profiles in Umbilical Veins: Insights into Vascular Dysfunctions of the Children Born after In Vitro Fertilization1

Abstract: Cardiovascular dysfunction and remodeling have been found in some children conceived by in vitro fertilization (IVF). However, the underlying mechanisms remain unclear. In this study, the retrospective investigation showed that the blood pressure of IVF-conceived Chinese children was higher than that of naturally conceived (NC) children at ages 3-13 yr. We analyzed the expression profile of proteins in the umbilical veins of IVF and NC newborns by proteomic techniques. Using iTRAQ (isobaric tags for relative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 45 publications
3
18
0
1
Order By: Relevance
“…The maternal characteristics and delivery data were comparable with the NC group, except levels LDL cholesterol, which is slightly elevated in IVF mothers (3.06 ± 0.73 VS 2.47 ± 0.66, P < 0.01). The serum estradiol concentration from umbilical cord blood vessels in IVF women was signi cantly higher than that in NC women, which is coincidence with our previous results [3]. However, there were no obvious differences in fetal birth weight or male birth rate between the NC and IVF born offspring.…”
Section: Baseline and Perinatal Characteristicssupporting
confidence: 90%
See 3 more Smart Citations
“…The maternal characteristics and delivery data were comparable with the NC group, except levels LDL cholesterol, which is slightly elevated in IVF mothers (3.06 ± 0.73 VS 2.47 ± 0.66, P < 0.01). The serum estradiol concentration from umbilical cord blood vessels in IVF women was signi cantly higher than that in NC women, which is coincidence with our previous results [3]. However, there were no obvious differences in fetal birth weight or male birth rate between the NC and IVF born offspring.…”
Section: Baseline and Perinatal Characteristicssupporting
confidence: 90%
“…We previously found that offspring born after IVF have a high blood pressure during age 3-13 years-old [3], so does offspring around 2 years-old recruited in our study (85.12 ± 5.23 VS 82.01 ± 4.85, P < 0.05) (Supplementary Table 1). Therefore, we focused on the endothelium-derived factors, such as endothelial nitric oxide synthase (eNOS), which is classical vasodilation factor, endothelin-1(ET1), one of the critical vasoconstriction factors, and vascular endothelial growth factor (VEGF), which is related with endothelial cell proliferation, angiogenesis, and vascular permeability.…”
Section: Endothelium-derived Factors Altered In Huvec Of Ivf Offspringmentioning
confidence: 51%
See 2 more Smart Citations
“…The absence of ovarian hyperstimulation in the VAO group may account for the lower incidence of hypertension when comparing to ICSI pregnancies. Furthermore, ovarian hyperstimulation has been reported to adversely affect cardiovascular and metabolic profile of children conceived with assisted reproductive technologies [19][20][21]; this is an interesting aspect to be evaluated in VAO children.…”
Section: Discussionmentioning
confidence: 99%